2006
DOI: 10.1194/jlr.m500387-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-dose simvastatin on triglyceride-rich lipoprotein metabolism in patients with type 2 diabetes mellitus

Abstract: Statins decrease triglycerides (TGs) in addition to decreasing low density lipoprotein-cholesterol. Although the mechanism for the latter effect is well understood, it is still unclear how TG decrease is achieved with statin therapy. Because hypertriglyceridemia is common in obese patients with type 2 diabetes mellitus, we studied triglyceride-rich lipoprotein triglyceride (TRL-TG) turnover in 12 such subjects using stable isotopically labeled glycerol. The diabetic subjects were studied after 12 weeks of plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 54 publications
3
25
1
1
Order By: Relevance
“…However, there was no association between the A/A or C/C genotypes with the fast metabolizer phenotype. To the best of our knowledge, this is the first report on the influence of rs5186 on ATV pharmacokinetics, though the rs5186 polymorphism has previously been associated with lipid levels (37), and ATV, as a statin, has lipid-lowering effects (38). Consistent with the present results, the C/C genotype has been related to higher levels of triglycerides in a healthy Malayan population (37).…”
Section: Discussionsupporting
confidence: 80%
“…However, there was no association between the A/A or C/C genotypes with the fast metabolizer phenotype. To the best of our knowledge, this is the first report on the influence of rs5186 on ATV pharmacokinetics, though the rs5186 polymorphism has previously been associated with lipid levels (37), and ATV, as a statin, has lipid-lowering effects (38). Consistent with the present results, the C/C genotype has been related to higher levels of triglycerides in a healthy Malayan population (37).…”
Section: Discussionsupporting
confidence: 80%
“…Though TG lowering is not the primary goal of statin treatment, recent studies demonstrating that high TG levels can cause CVD 3,4 and that TG levels may be responsible for some of the residual CVD risk in statin-treated individuals 5,6 highlight the value of understanding how statin treatment changes plasma TG levels [42][43][44][45][46][47][48] and increasing both preheparin plasma lipase activity and postheparin LPL activity, 43 while other studies have indicated that statins reduce VLDL-TG secretion and VLDL particle size. [49][50][51] It is possible that the mechanism by which statins reduce plasma TG levels could depend on an individual's baseline fractional catabolic rates and production rates.…”
Section: Discussionmentioning
confidence: 99%
“…Òðàíçèöèÿ íóêëåîòèäîâ + 495T>G â 8 èíòðîíå ãåíà LPL, áîëåå èçâåñòíàÿ êàê Hind III ïîëèìîðôèçì, îïðå-äåëÿåò íàëè÷èå (àëëåëü H+) èëè îòñóòñòâèå (àëëåëü Í-) ó÷àñòêà óçíàâàíèÿ äëÿ ýíäîíóêëåàçû HindIII [6]. Íîñèòåëüñòâî àëëåëüíîãî âàðèàíòà + 495G (Í-) àññî-öèèðîâàíî ñ ïîâûøåííîé àêòèâíîñòüþ è/èëè ýêñïðåñ-ñèåé ôåðìåíòà è ñâÿçàííûì ñ ýòèì ïîâûøåííûì ãèä-ðîëèçîì ÒÃ, óâåëè÷åíèåì óðîâíÿ ÕÑ ËÂÏ [15] è ïîíè-aeåííûì ðèñêîì ðàçâèòèÿ êîðîíàðíîãî àòåðîñêëåðîçà [10,14].…”
Section: ðåçóëüòàòû è èõ îáñóAeäåíèåunclassified